Global, regional, and national burden of forearm fracture from 1990 to 2021: a study based on GBD 2021 - Cheng Chen; Cheng Chen; ShuTao Zhang; ZhenDong Li; HaiChao Zhou; Jiang Xia; Bing Li; YunFeng Yang (Frontiers in Public Health)
ObjectiveTo comprehensively examine the regional, national, and global burden and trends of forearm fractures from 1990 to 2021.MethodsThe incidence and years lived with disability (YLDs), with uncertainty interval (UI), for forearm fractures from 1990 to 2021 were extracted from the Global Burden of Disease 2021. The temporal, geographical, and demographic burden of forearm fractures was assessed, as well as the leading causes. Finally, a decomposition analysis was performed.ResultsIn 1990, the incidence number of forearm fractures globally was 26,098,810 (95% UI: 20,967,988–32,372,267), which increased to 31,905,396 (95% UI: 25,403,829–39,982,115) in 2021. The age-standardized incidence rate was 483.28 (95% UI: 387.42–599.37) in 1990 and decreased to 402.35 (95% UI: 319.86–505.21) in 2021. In 1990, the global number of YLDs due to forearm fractures was 144,166 (95% UI: 87,129–229,017), which increased to 205,031 (95% UI: 126,061–320,235) in 2021. The age-standardized YLDs rate was 2.98 (95% UI: 1.82–4.7) in 1990, which decreased to 2.51 (95% UI: 1.54–3.93) in 2021. Females showed a higher burden than males, and the incidence rate of forearm fractures exhibited a bimodal distribution, peaking in youth and older adulthood. Recently, the disease burden presented a challenge due to the aging population. Falls were the most prominent cause of forearm fractures, followed by road injuries and exposure to mechanical forces.ConclusionForearm fractures have increased in incidence and YLDs number since 1990, particularly among females. The incidence rate follows a bimodal distribution, with peaks in youth and older adulthood. The age-related burden has progressively shifted toward older populations, reflecting trends in global aging. Falls remain the leading cause of forearm fractures, with the highest burden observed among older adult females.